2015
DOI: 10.1016/j.biomaterials.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen matrix deposited on the surface of biomaterials acts as a natural anti-adhesive coating

Abstract: Adsorption of fibrinogen on the luminal surface of biomaterials is a critical early event during the interaction of blood with implanted vascular graft prostheses which determines their thrombogenicity. We have recently identified a nanoscale process by which fibrinogen modifies the adhesive properties of various surfaces for platelets and leukocytes. In particular, adsorption of fibrinogen at low density promotes cell adhesion while its adsorption at high density results in the formation of an extensible mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
(70 reference statements)
2
42
1
Order By: Relevance
“…It has been shown that hard, rough surfaces such as modified titanium and stainless steel have increased monocyte and leukocyte adhesion compared to surfaces with more yield and lower surface roughness, such as multilayered fibrinogen and our nanomatrix coating. 3335 Our previous studies have demonstrated that our nanomatrix coating forms a stable, smooth, uniform surface on stents; this may be a critical factor in prevention of inflammatory cell adhesion. 25 Thus, the nanomatrix coating itself may be protective under flow against inflammatory cell adhesion, although the addition of NO increased this protection.…”
Section: Resultsmentioning
confidence: 94%
“…It has been shown that hard, rough surfaces such as modified titanium and stainless steel have increased monocyte and leukocyte adhesion compared to surfaces with more yield and lower surface roughness, such as multilayered fibrinogen and our nanomatrix coating. 3335 Our previous studies have demonstrated that our nanomatrix coating forms a stable, smooth, uniform surface on stents; this may be a critical factor in prevention of inflammatory cell adhesion. 25 Thus, the nanomatrix coating itself may be protective under flow against inflammatory cell adhesion, although the addition of NO increased this protection.…”
Section: Resultsmentioning
confidence: 94%
“…8,[30][31][32][33] This region has also been directly correlated with adhesion events. [34][35][36] Fibrinogen aC region (221-610) is composed of a flexible aC connector (221-391) and a more structured aC domain (392-610). 4,7 During fibrin polymerization, crosslinking in the aC region has been shown to promote lateral aggregation and protofibril staggering.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, at low-density, fibrinogen forms a monolayer that directly attaches to the NP surface, 74 leading to high adhesion with platelets and leukocytes. While at high density, the fibrinogen molecules form an extensible multilayer matrix by self-assembly through the interaction between their αC domains, 75,76 this dramatically decrease cellular association under both static and flow conditions. 74,77 These results can suggest a new approach for synthesis and development of biomaterials, specifically in implantation in order to decrease initial thrombogenesis.…”
mentioning
confidence: 99%